Walking versus running and GFR trajectory in healthy young adults - Ronit Calderon-Margalit; Ruth Lev Bar-Or; Arnon Afek; Dorit Tzur; Dana Levin; Dror Ben-Ruby; Ariel Furer; Gilad Twig; Karl Skorecki; Asaf Vivante (PLoS ONE, 2025)
Background The effect of physical activity on the primary prevention of chronic kidney disease (CKD) is unclear. We assessed walking and running as exercise behaviors and their associations with individual-level risk for kidney function decline. Methods We conducted a historical cohort study in which we followed 20,976 young adults. Participants were interviewed periodically about their lifestyle, and clinical parameters were assessed. The decline in estimated glomerular filtration rate (eGFR) over time was divided into quartiles. Using logistic regressions, we estimated the odds ratio (OR) for being in the slowest declining quartile by consistency of running or walking. We also used Cox proportional hazards models to estimate the associations of physical activity with future eGFR < 90 ml/min/1.73m2. All models were adjusted for age, sex, smoking status, family history of kidney diseases, BMI, blood-pressure, baseline eGFR and serum cholesterol. Results During 9.5 years of follow-up, the eGFR decreased by 0.97 ml/min/1.73m2 per year. Participants who reported in two consecutive questionnaires on walking as a leisure time activity had an OR of 1.21 (95% confidence interval: 1.03–1.41) to have slow eGFR decline compared to those who were physically inactive. Participants who predominantly reported on running as their physical activity were less likely to be slow eGFR decliners (OR:0.81, 95% CI:0.71–0.93). Similarly, consistent walking was associated with decreased risk for future eGFR < 90 ml/min/1.73m2 in contrast to consistent running which was associated with an increased risk for reduced eGFR. All associations showed dose dependent effects in terms of the number of weekly activity sessions. Conclusions Consistent walking, as opposed to consistent running, was associated with slower eGFR decline compared to inactive participants. These associations start already within the normal GFR range.